A Democracia em Marx: o contexto do surgimento e a ambivalência do conceito - Müller, Marcos Lutz (Revista Eletrônica Estudos Hegelianos, 2018)
After a short characterization of the concept of democracy in its classical and ancient meaning (1), after a brief reference to the transformations it underwent by late 18th  century (2) and both to its consolidation as representative democracy and to the signs of exhaustion pertaining political representation (3), this article shows how Marx’ approach to democracy departs from the modern separa tion between civil society and state, first conceptually established by Hegel, and how the sublation (Aufhebung) of modern civil society’santagonisms within the state’s “concrete universal”, as suggested by Hegel, is an “illusory” overcoming (4). But the young Marx’ critique of Hegel’s Philosophy of Right, of speculative dialectic’s “false positivism”  and the transcendent character of political state does not hinder his partaking of some of Hegel’s most central political theses and, in The Capital, of certain aspects of the dialectical “presentation” (Darstellung ) (5, 6). Marx diagnoses and critiques the Hegelian attempt at overcoming modern civil society’s antagonisms and atomism  by means of a political representation through estates and corporations as an historical regression and as aconfirmation of social atomism and the individual’s isolation (7). He inverts Hegel’s claim that “the individuals” participate “as a whole” within the state’s universal issues into the claim that “all individuals as singulars” –  i.e., as “generic”, entirely socialized singulars of a society which does not determines itself by aliena ted work and private property –  realize universality (classically thought of as political) within non-atomized social relations of “human common -being (Gemeinwesen)” (8, 9). In this realization of  the political universal within the immanence of human “common -being”, to be reached by means of active and passive universal suffrage, democracy’s ambivalence comes to light, now considered in the dynamics of the dissolution of the democracy which is still “democratic republic” into the “true democracy”, conceived of as the “people’s self -determination”  and the sublation of the opposition between the social and political spheres (10, 11, 12). Thus, Marx’s original insight pertaining the critique of the autonomy and transcendence of the political sphere leads to the concept of a radical democracy, whose “constitution” (in its ontological meaning) results out of a continuous creation of the people’s sovereign will, which brings the “true human common -being” i nto effectivity (13).